2024
DOI: 10.1002/hsr2.1954
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the systemic immune‐inflammation index in type 2 diabetic patients with and without dry eye disease: A case‐control study

Amani Y. Alhalwani,
Shatha Jambi,
Anwar Borai
et al.

Abstract: BackgroundThe inflammation plays a role in the pathophysiology of type‐2 diabetes progression, and the mechanism remains unclear. The systemic immune‐inflammation index (SII) is a novel inflammatory marker for type 2 diabetes patients and integrates multiple indicators in complete blood counts and routine blood tests.AimSince there is no international diagnostic standard for dry eye disease (DED), this study uses low‐cost inflammatory blood biomarkers to investigate the correlation between SII and DM2–DED and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…The following systematic inflammation index ratios were subsequently calculated: the NLR, which was calculated by dividing the neutrophil count by the lymphocyte count [ 45 ]; the PLR, which was calculated by dividing the platelet count by the lymphocyte count [ 45 ]; the MLR, which was calculated by dividing the monocyte count by the lymphocyte count [ 50 ]; and the NLPR, which was calculated by dividing the neutrophil count by the lymphocyte count multiplied by the platelet count [ 44 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following systematic inflammation index ratios were subsequently calculated: the NLR, which was calculated by dividing the neutrophil count by the lymphocyte count [ 45 ]; the PLR, which was calculated by dividing the platelet count by the lymphocyte count [ 45 ]; the MLR, which was calculated by dividing the monocyte count by the lymphocyte count [ 50 ]; and the NLPR, which was calculated by dividing the neutrophil count by the lymphocyte count multiplied by the platelet count [ 44 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, numerous studies have indicated that the neutrophil-to-lymphocyte and platelet ratio (NLPR) is a novel inflammatory marker and essential predictor of inflammation in several inflammatory diseases, including COVID-19 [ 42 44 ]. Few studies have examined the relationship between chronic diseases and dry eye disease using blood biomarkers, such as inflammation index ratios [ 45 47 ]. Additionally, a study in which the association between DED and lipid profiles was investigated revealed that the results of participants with DED were similar to the results of those diagnosed with DLP compared with the healthy group [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Raised levels of NLR and PLT/Ly have been associated with DED. The value of the systemic immune inflammation (SII) index has been used as a prognostic indicator for inflammatory diseases such as DM2 [29].…”
Section: Platelets To Lymphocytes Ratio (Plt/ly)mentioning
confidence: 99%